Analysis of the disease burden trend of malignant tumors of the female reproductive system in China from 2006 to 2020 - Xiting Han; Zhihong Wang; Dongmei Huang; Kehong Deng; Qian Wang; Cancan Li; Jicun Zhu (BMC, 2022)
Plain English summary Malignant tumors of the female reproductive system are the leading causes of women's mortality worldwide, mainly including cervical cancer, uterine cancer and ovarian cancer. Numerous studies have reported mortality changes in the three primary reproductive system cancers among different countries, with inconsistent temporal trends. In 2020, almost 17.51% of malignant tumors of the female reproductive system deaths occurred in China because of the large population base and severe aging. However, there are limited studies on the disease burden of malignant tumors of the female reproductive system in China. This study analyzed the mortality, YLL and LLE of cervical cancer, uterine cancer and ovarian cancer using the National Death Cause Surveillance Dataset from 2006 to 2020. The findings revealed that mortality and disease burden of malignant tumors of the reproductive system showed no significant change. The mortality and disease burden of uterine cancer decreased significantly, but that of cervical cancer and ovarian cancer remain high. Cervical cancer has a higher mortality and disease burden than uterine cancer and ovarian cancer, making it the most severe malignant tumor of the female reproductive system. Screening and HPV vaccination will reduce the mortality and disease burden of cervical cancer in China, but this effect will take many years to manifest. Screening and prevention strategies for high-risk groups of uterine cancer and ovarian cancer should be established as soon as possible. In summary, the management and monitoring of malignant tumors of the female reproductive system should be strengthened.